2006
DOI: 10.1248/bpb.29.1431
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Yukmijihwang-tang Derivatives (YMJd) on Ibotenic Acid-Induced Amnesia in the Rat

Abstract: The consistent findings in Alzheimer's disease (AD) patients are impairment in cognitive performances such as attention, learning and memory, and change of cholinergic markers, including levels of acetylcholine (ACh) and choline acetyltransferase (ChAT). [1][2][3] Since cholinergic deficits are found to be associated with cognitive decline or dementia, increase of the central cholinergic system by selective inhibition of cholinesterase is one of the more promising current therapeutic tools for treating AD.4) C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 33 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…Traditionally, Yukmijihwang-tang is applied in treating renal disorders, diabetes mellitus, and neurosis [13]. There have been many studies on the pharmacological effects of Yukmijihwang-tang, such as protection against renal ischemia/reperfusion [14], memory enhancement [15], stimulation of spermatogenesis [16], inhibition of bone loss [17], anti-asthmatic effects [18] and antidiabetic effects [13]. Although many researchers have investigated the pharmacological effects of Yukmijihwang-tang, there has been no study on its possible protective effects against BPH.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, Yukmijihwang-tang is applied in treating renal disorders, diabetes mellitus, and neurosis [13]. There have been many studies on the pharmacological effects of Yukmijihwang-tang, such as protection against renal ischemia/reperfusion [14], memory enhancement [15], stimulation of spermatogenesis [16], inhibition of bone loss [17], anti-asthmatic effects [18] and antidiabetic effects [13]. Although many researchers have investigated the pharmacological effects of Yukmijihwang-tang, there has been no study on its possible protective effects against BPH.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PM012 treatment accelerated the speed of information processing and enhanced cognitive abilities in normal subjects [28]. PM012 may repair cognitive impairment induced by dementia through an increase of acetylcholine synthesis in combination with the other advantageous effects mentioned above, thus helping to alleviate the symptoms of dementia patients [15,27,28]. …”
Section: Discussionmentioning
confidence: 99%
“…Ancient Chinese herbal textbooks also reference YMJ as an anti-aging treatment. In a previous study, YMJ derivatives (PM012) containing Lycii fructus , in addition to the other components of YMJ, enhanced memory retention by protecting neuronal cells and enhancing cell proliferation and neurite growth [15]. In addition, PM012 accelerated the speed of information processing and enhanced cognitive abilities in normal subjects [16].…”
Section: Introductionmentioning
confidence: 99%
“…YMJ has been used traditionally for the treatment of renal diseases, edema, diabetes, neurosis, and aging in Korea and China. Modern research has reported various biological activities of YMJ or YMJ derivatives (YMJD), such as antiosteoporotic [ 2 , 3 ], antiamnesia [ 4 , 5 ], antiasthmatic [ 6 ], and memory-enhancing [ 7 ] effects. In addition, our group recently reported the efficacy of YMJ treatment against benign prostatic hyperplasia in vivo [ 8 ].…”
Section: Introductionmentioning
confidence: 99%